DOI: 10.17077/etd.qpvbon5z
|View full text |Cite
|
Sign up to set email alerts
|

An infinite family of links with critical bridge spheres

Abstract: A closed, orientable, splitting surface in an oriented 3-manifold is a topologically minimal surface of index n if its associated disk complex is (n−2)-connected but not (n−1)-connected. A critical surface is a topologically minimal surface of index 2. In this paper, we use an equivalent combinatorial definition of critical surfaces to construct the first known critical bridge spheres for nontrivial links.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 10 publications
1
12
0
Order By: Relevance
“…This implies that the unknot in 3-bridge position has a corresponding bridge sphere whose index is at most 2, and in fact it is critical. In [13], we constructed a family of 4-bridge links and showed that their corresponding bridge spheres are critical, demonstrating the existence of critical bridge spheres for nontrivial multicomponent links. This paper generalizes that result, showing that for every b ≥ 3, there is an infinite family of b-bridge links whose corresponding bridge spheres are critical.…”
Section: Introductionmentioning
confidence: 94%
See 4 more Smart Citations
“…This implies that the unknot in 3-bridge position has a corresponding bridge sphere whose index is at most 2, and in fact it is critical. In [13], we constructed a family of 4-bridge links and showed that their corresponding bridge spheres are critical, demonstrating the existence of critical bridge spheres for nontrivial multicomponent links. This paper generalizes that result, showing that for every b ≥ 3, there is an infinite family of b-bridge links whose corresponding bridge spheres are critical.…”
Section: Introductionmentioning
confidence: 94%
“…Under the isotopy of F taking F from level 1 to level h, the loop ∂B becomes incredibly convoluted. In [13], the author describes a convenient way to represent the image of ∂B under this isotopy using the unlink diagram in Figure 4. To obtain Figure 4, we use the fact that the signs of the rows of twist regions alternate, but we refer readers to [13] for more detail.…”
Section: The Labyrinthmentioning
confidence: 99%
See 3 more Smart Citations